THE EFFORTS TO INCREASE STUDENTS ACTIVENESS IN LEARNING MATHEMATICS BY USING COOPERATIVE LEARNING MODELS TYPE TEAM ASSISTED INDIVIDUALIZATION (TAI) - Yerra Destiyari; Nur Arina Hidayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
The student activity still low, so it gives the effect of the result in learning mathematics. This research aims to improve student activity in learning mathematics by using cooperative learning models type Team Assisted Individualization (TAI) of VII D grade in SMP Muhammadiyah 1 Yogyakarta in the academic year 2016/2017. The type of research used is classroom action research (CAR) consists of two cycles. The research setting is students of VII D grade in SMP Muhammadiyah 1 Yogyakarta in the academic year 2016/2017 with the implementation of cooperative learning models type of Team Assisted Individualization with the subject of the concept of square and rectangular geometry in problem-solving. The data collection techniques are observation, interview, documentation, test, and triangulation. The data collection instrument is the observation sheets of students and teachers—the analysis data using descriptive qualitative analysis. The result of the research shows that mathematics learning using a cooperative learning model type of TAI can increase the student's activeness in learning mathematics at VII D grade SMP Muhammadiyah 1 Yogyakarta in the academic year 2016/2017. It showed from the result of the observation that learning mathematics has increased in every cycle, such as in cycle I, the percentage of student activeness of 59,27% with sufficient criteria, and in cycle II increase up to 78,76% with good criteria. Also, the outcome of students learning in each cycle increases.